Development and tolerability of a novel virtual- and proprioception-based car crash simulator as a new research tool in motor vehicle trauma research - Lukacs, Michael J.; Babin, Mathias; Dickey, James P.; Melling, C. W. James; Walton, David M. (Frontiers in Virtual Reality, 2023)
Purpose: Investigations of causal theories of neck pain (NP) following motor vehicle crashes (MVC) has been difficult, as simulation is limited. Thus, we sought to evaluate tolerability to a novel virtual reality (VR)-based road collision simulator and screen for adverse reactions. Materials and Methods: Cross-sectional study. 25 healthy participants were exposed to a novel VR-based rear-end MVC with a small perturbation (0.2 g). The Simulator Sickness Questionnaire (SSQ) and Presence Questionnaire (PQ) were measured post-exposure and adverse reactions were recorded. Results: The system was well tolerated with no adverse reactions, however one participant reported NP the following day not lasting longer than 48 hours. Participants reported low levels of simulator sickness (mean SSQ =23.49 + 21.98, range = 0.00 to 89.76; max score = 235.62), while presence (mean PQ = 91.04 + 14.08, range = 54.00 to 112.00; max score = 133), was lower than literature recommendations. Conclusions: A VR-based road collision simulator can be safely used to explore the phenomenon of a MVC under controlled circumstances. Future work is needed to optimize the VR environment and to investigate the effects of crash parameters.